2009
DOI: 10.1002/dmrr.1041
|View full text |Cite
|
Sign up to set email alerts
|

Association of the metabolic syndrome with depression and anxiety in Japanese men: A 1‐year cohort study

Abstract: Our results suggest that MetS is a predictive factor for the development of depression, and that waist circumference largely contributes to the association between MetS and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 24 publications
6
57
2
Order By: Relevance
“…The prevalence (36.5% in men, 37.6% in women) of depressive symptoms (CES_D score C16) among our study population is much higher than that reported in studies on Western populations but is similar to that reported in a previous large-scale study of Japanese workers (38.3% in men, 39.8% in women) [20]. Metabolic syndrome has been shown to be associated with depressive symptoms in studies performed in Western countries [7,9,[21][22][23][24][25][26] and Japan [8,10], although the association is not entirely consistent [11,12]. This inconsistency could be ascribed to the difference in the criteria of depressive symptoms and metabolic syndrome across studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The prevalence (36.5% in men, 37.6% in women) of depressive symptoms (CES_D score C16) among our study population is much higher than that reported in studies on Western populations but is similar to that reported in a previous large-scale study of Japanese workers (38.3% in men, 39.8% in women) [20]. Metabolic syndrome has been shown to be associated with depressive symptoms in studies performed in Western countries [7,9,[21][22][23][24][25][26] and Japan [8,10], although the association is not entirely consistent [11,12]. This inconsistency could be ascribed to the difference in the criteria of depressive symptoms and metabolic syndrome across studies.…”
Section: Discussionsupporting
confidence: 87%
“…This inconsistency could be ascribed to the difference in the criteria of depressive symptoms and metabolic syndrome across studies. Many earlier studies [7,9,11,24,25] used NCEP-ATP criteria, which we also adopted in our study, whereas others used the criteria of the International Diabetes Foundation (IDF) [8,10,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various clinical studies have co-related MetS with depression and depressive symptoms, irrespective of gender, obesity status and type 2 diabetes. 22,23 MetS has been linked with depression through functions of HPA axis. Loss of Glucocorticoid receptors may alter hypothalamus-pituitary-adrenal (HPA)-axis regulation.…”
Section: Introductionmentioning
confidence: 99%